Sustainable development goals and corporate financial performance: examining the influence of stakeholder engagement - Lin, Woon Leong; Chong, Siong Choy; Wong, Kelly Kai Seng (John Wiley and Sons, 2024)
This study investigates the relationship between sustainable development goals (SDG) and corporate financial performance (CFP) in the motor vehicle manufacturing sector. Using a comprehensive dataset from CSRHUB database, covering 380 companies from 2016 to 2022, we analyze how SDG-related disclosures—across depth, breadth, and concentration—impact financial metrics such as return on assets (ROA), return on equity (ROE), return on invested capital (ROIC), and Tobin's Q. The study employs the system generalized method of moments (System GMM) to mitigate endogeneity concerns, ensuring robust results. Our findings reveal that while SDG initiatives positively influence CFP, the role of stakeholder engagement is pivotal. Firms with comprehensive SDG strategies and high stakeholder engagement experience superior financial outcomes. However, an overly narrow focus on specific SDG themes, even with strong stakeholder interactions, correlates with weaker financial performance. This research contributes to the ongoing discourse on corporate sustainability by highlighting the moderating effect of stakeholder engagement in SDG disclosures. The findings offer practical implications for both policymakers and business leaders, suggesting a balanced approach to SDG reporting to maximize financial performance.